Dinâmica pré e pós-colostral de parâmetros bioquímicos em cordeiros - Souza, Damaris Ferreira De; Monteiro, Alda Lúcia Gomes; Dittrich, Rosangela Locatelli; Schmidt, Elizabeth Moreira Dos Santos [UNESP]; Fernandes, Sergio Rodrigo; Beltrame, Olair Carlos (Universidade Federal de Goiás, 2014)
This study aimed to verify the influence of colostrum in serum biochemical parameters in newborn lambs. Blood samples were taken of 28 lambs, determining the protein, energy and kidney function indicators, bilirrubins and the enzymes aspartate aminotransferase (AST), gamma-glutamyl transferase (GGT) and creatine kinase (CK), in pre and post-colostrum moments. The data were analyzed comparing the variability of the parameters between the two moments. There was an elevation (P<0.001) in total protein concentrations, in response to substantial increase (P<0.01) in total globulin levels, and a slight decrease (P<0.05) in albumin concentration, after colostral intake. We also observed higher values of total and conjugated bilirubins (P<0.001), and variation of kidney metabolites, with an elevation of urea levels (P<0.01) concomitant to decrease of creatinine values (P<0.001) in the post-colostrum moment. There was an increase (P<0.001) in glycemia, total cholesterol and triglycerides, as well as of the enzymatic activities (P<0.001) of AST and GGT, between the moments evaluated. In conclusion, the dynamics of biochemical profile in newborn lambs suffers the effect of colostrum intake and of adaptations of physiological functions to extrauterine life. The parameters values vary markedly in the postnatal period, being recommended to use proper reference values for this phase.

O objetivo deste estudo foi verificar a influência do colostro nos parâmetros bioquímicos séricos em cordeiros recém-nascidos. Foram colhidas amostras sanguíneas de 28 cordeiros, determinando-se os indicadores proteicos, energéticos, de função renal, bilirrubinas e as enzimas aspartato aminotransferase (AST), gama-glutamiltransferase (GGT) e creatina quinase (CK), nos momentos pré e pós-colostro. Os dados foram analisados comparando-se a variabilidade dos parâmetros entre os dois momentos. Houve elevação (P<0,001) das concentrações de proteínas totais, em resposta ao forte aumento (P<0,01) dos teores de globulinas totais e ao leve decréscimo (P<0,05) da concentração de albumina, após a ingestão colostral. Também foram observados maiores valores de bilirrubinas total e direta (P<0,001), e variação dos metabólitos renais, com elevação dos níveis de ureia (P<0,01) concomitante à redução dos valores de creatinina (P<0,001), no momento pós-colostro. Houve aumento (P<0,001) da glicemia, de colesterol total e triglicerídeos, bem como das atividades enzimáticas (P<0,001) de AST e GGT, entre os momentos avaliados. Conclui-se que a dinâmica do perfil bioquímico em cordeiros recém-nascidos sofre o efeito da ingestão de colostro e da adaptação das funções fisiológicas à vida extra-uterina. Os valores dos parâmetros variam marcadamente no período pós-natal, sendo recomendável a utilização de valores de referência próprios para esta fase.
Pre and post-colostral dynamics of biochemical parameters in lambs
Keywords: amamentação; bioquímica clínica; neonato; ovino; sangue; blood; clinical biochemistry; neonate; nursing; sheep